Occurrence and abundance of copepods in zooplankton assemblages at Sonmiani Bay, northern Arabian Sea - Shumaila Mubarak; Qadeer Muhammad Ali (Journal of Marine Studies, 2026)
This research study reports the first data on seasonal assessment of copepod-specific distribution in Sonmiani Bay. It provides a baseline dataset for future study of planktonic biodiversity in the region by documenting seasonal variations in species-level abundance and related environmental parameters. Zooplanktons were sampled during the high tide with seasonal intervals, i.e., Intermonsoon (April), Southwest monsoon (July), Intermonsoon (October), and Northeast monsoon (January). Physicochemical parameters of water were also recorded in situ on a seasonal basis. A total of 41 copepod species across 23 genera and 17 families were identified, with Calanoida emerging as the dominant order. Centropages dorsispinatus, Subeucalanus crassus, Labidocera pectinata, and Acartia spinicauda showed seasonal dominance during the study period. Principal component analysis (PCA) revealed that water temperature, salinity, and dissolved oxygen were the primary drivers of copepod distribution, with PC1 explaining 37.2% and PC2 24.2% of the total variance (Eigenvalues: 4.09 and 2.66, respectively). The study reveals the ecological importance of copepods within the zooplankton assemblages at Sonmiani Bay and provides baseline data for future biodiversity monitoring and management in the coastal waters of Pakistan.